1996
DOI: 10.1177/106689699500300306
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Distribution in Mucocutaneous Biopsies of Human Paracoccidiomycosis

Abstract: The authors studied the distribution of Paracoccidioides brasiliensis antigen(s) in human skin and oral mucosa. In biopsies obtained from untreated patients showing the chronic form of the disease, the authors demonstrated the P. brasiliensis antigen using two polyclonal immune sera raised in rabbits, one against the exoantigens of P. brasiliensis and the other against a 43-kDa glycoprotein. Langerhans' cells were detected through double immunolabeling using an anti-S 100 protein monoclonal antibody. Double la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Studies have also reported a reduced number of epidermal Langerhans cells (LCs) with short and irregular dendrites when compared with the normal skin (Gimenez et al , 1987; Pagliari and Sotto, 2003). In addition, Sandoval et al (1996) did not detect Pb antigens in the cytoplasm of LCs, suggesting that they would not be capable of presenting fungal antigens efficiently. Conversely, the yeast has been described inside FXIIIa+ dermal dendrocytes, another group of dendritic cells with characteristics similar to LCs (Pagliari and Sotto, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…Studies have also reported a reduced number of epidermal Langerhans cells (LCs) with short and irregular dendrites when compared with the normal skin (Gimenez et al , 1987; Pagliari and Sotto, 2003). In addition, Sandoval et al (1996) did not detect Pb antigens in the cytoplasm of LCs, suggesting that they would not be capable of presenting fungal antigens efficiently. Conversely, the yeast has been described inside FXIIIa+ dermal dendrocytes, another group of dendritic cells with characteristics similar to LCs (Pagliari and Sotto, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…Antigen(s) were also observed in the cytoplasm of proliferated and hypertrophic FXIIIa + DD. Similar to paracoccidiodomycosis 11,16 both probably function as antigen‐ presenting cells (APCs) in chromoblastomycosis. Langerhans' cells in the dermis appeared to be conspicuous and occasionally were part of the granulomatous inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, macrophages are considered central to the anti-Pb immunity [36]. Neutrophil accumulation has been described in the early phase of the immune response, either permeating the granulomatous reaction or forming microabscesses within them [37][38][39][40]. These cells have been shown to also exert in vitro anti-Pb activity [41][42][43][44], but their in vivo role in the host defense against the fungus remains to be determined.…”
mentioning
confidence: 99%